Development of Mathematics Teaching Materials to Improve Higher Order Thinking Skills in Grade 3rd Students in Elementary School - Ratnawati, Wahyu; Sutama; Sabar Narimo (JTP - Jurnal Teknologi Pendidikan, 2022)
Mathematics learning in elementary schools is not fully oriented to higher order thinking skills (HOTS). In fact, HOTS play an important role in solving mathematical problems so that they require the support of effective teaching materials. The purpose of this study was to develop mathematics teaching materials to improve HOTS in grade 3 elementary school students. This research is a development research using the Borg & Gall model. The stages of this research consist of information gathering, development planning, product draft development, and initial product testing. Research data obtained through questionnaires and tests. The data were then analyzed using an interactive model consisting of data condensation, data presentation, and drawing conclusions. The results showed that the product assessment results from material experts were 88.09, media experts were 92.00, linguists were 92.30, and practitioners were 92.24. Considering the results of the validation assessment from several experts, it can be concluded that the mathematics teaching materials developed have been feasible to improve HOTS in grade 3 elementary school students. The development of 3D-based mathematics teaching materials on two-dimentional figure provides assistance for students in solving problems more realistically and easily. Book products are not only in the form of pictures but can be seen, folded or rotated so that they can develop students' thinking in analyzing, evaluating and creating which are adapted to the context of solving mathematical problems in elementary schools.